2019
DOI: 10.17352/gjfr.000013
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Premature Ovarian Insuffi ciency and prevalence of medical diseases

Abstract: Background: Premature Ovarian Failure (POF) represents 1% among women below the age of 40 and can be diagnosed by two levels of serum Follicular Stimulating Hormone (FSH) ≥40mIU/mlat 6 weeks apart. There are many reasons for POF and commonly is idiopathic (60% to 80%). POF has a negative impact on the psychological, social and quality of life of females.Objective: This study aims to fi nd the possibility of prediction of Premature Ovarian Insuffi ciency (POI) and its relation to medical disorders. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…3 However, in POI, intermittent and unpredictable resumption may occur in ovarian activity. 4 European society of human reproduction and endocrinology (ESHRE) has confirmed the term POI for research and clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, in POI, intermittent and unpredictable resumption may occur in ovarian activity. 4 European society of human reproduction and endocrinology (ESHRE) has confirmed the term POI for research and clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The ovulatory disorder is essential issue regarding the female fertility [3]. There are many factors affecting the ovarian function (ovulation) including genetic (chromosomal), infection, polycystic ovary, iatrogenic (chemotherapy and radiotherapy), endocrine disorders (diabetes mellitus, thyroid problem, hyperprolactinemia) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Various research revealed that the most common endocrine abnormalities interfere with the ovulation is thyroid problem which consequently ended by Premature Ovarian Insufficiency (POI) [5]. From the gynecology point view, thyroid dysfunction could carry irregularity in menstrual cycle, unovulatory cycles, POI, infertility and even if the patient conceive could carry a high miscarriage rate, low live birth rate [6,7].…”
Section: Introductionmentioning
confidence: 99%